Modulation of Phenotype and Function of Human CD4+CD25+ T Regulatory Lymphocytes Mediated by cAMP-Elevating Agents - Riccomi, Antonella; Gesa, Valentina; Sacchi, Alessandra; De Magistris, Maria Teresa; Vendetti, Silvia (Frontiers in Immunology, 2016)
We have shown that cholera toxin (CT) and other cyclic AMP (cAMP)-elevating agents induce upregulation of the inhibitory molecule CTLA-4 in human resting CD4+ T lymphocytes, which following the treatment acquired suppressive functions. In this study, we evaluated the effect of cAMP-elevating agents on human CD4+CD25+ T cells, which include the T regulatory cells (Tregs) that play a pivotal role in the maintenance of immunological tolerance. We found that cAMP-elevating agents induce upregulation of CTLA-4 in CD4+CD25− and further enhance its expression in CD4+CD25+ T cells. We observed an increase of two isoforms of mRNA coding for the membrane and the soluble CTLA-4 molecules, suggesting that the regulation of CTLA-4 expression by cAMP is at the transcriptional level. In addition, we found that the increase of cAMP in CD4+CD25+ T cells converts the CD4+CD25+Foxp3− T cells in CD4+CD25+Foxp3+ T cells, whereas the increase of cAMP in CD4+CD25− T cells did not upregulate Foxp3 in the absence of activation stimuli. To investigate the function of these cells, we performed an in vitro suppression assay by culturing CD4+CD25+ T cells untreated or pre-treated with CT with anti-CD3 mAbs-stimulated autologous peripheral blood mononuclear cell. We found that CT enhances the inhibitory function of CD4+CD25+ T cells, CD4+, and CD8+ T cell proliferation and IFNγ production are strongly inhibited by CD4+CD25+ T cells pre-treated with cAMP-elevating agents. Furthermore, we found that CD4+CD25+ T lymphocytes pre-treated with cAMP-elevating agents induce the upregulation of CD80 and CD86 co-stimulatory molecules on immature dendritic cells (DCs) in the absence of antigenic stimulation, however without leading to full DC maturation. These data show that the increase of intracellular cAMP modulates the phenotype and function of human CD4+CD25+ T cells.